Work Stress Patterns, Sources and Coping Strategies: A Study of Malaysian and Jordanian Customs Employees - Barhem, Belal (2002)
There have been many studies on work stress, and many descriptions of it. The multi-dimensionality of stress is evidenced by the fact that it takes different forms and occurs in different fields. This study aimed to evaluate the levels and major sources of work stress that afflict two countries customs employees (Malaysian and Jordanian), and the possible strategies to cope with the stress. It also aimed to investigate the Malaysian and Jordanian customs employees on their levels and sources of work stress, and their coping strategies used. Finally, it sought to rank the sources of work stress and coping strategies in their relationships to personal feelings. The study comprised of 216 respondents from the Malaysian customs and 248 respondents from the Jordanian customs. Path analysis, multiple stepwise regression and correlation analysis were the major statistical tools used to analyse the data.The major findings of the study were that: - a) Both the Malaysian and Jordanian customs suffered from high work stress. b) Role ambiguity was the most potent cause of both medium and high-level stress in the Jordanians. The major causes for the Malaysians were role overload qualitative for medium level stress and role ambiguity for high level stress. c) Flexibility was the major coping strategy against both medium and high stress by the Jordanians. The Malaysians used active & productive against medium level stress and acceptance of others values against high-level stress. In addition, the study clarified the relationships between the dependent and independent variables used in the model. Significant relationships were found for sources of work stress with the levels of work stress and coping strategies in both countries. The relationships between personal differences and sources of work stress were weak, although significant, in both countries, while the relationships between personal difference on one side, and the levels of work stress and coping strategies on the other were not significant in the Jordanian case. In the Malaysian case, the relationship between personal differences and level of work stress and coping strategies were significant. The relationships between levels of work stress and coping strategies were not significant in the Jordanian case. But significant for the Malaysians. The relationships between the levels and sources of work stress were significant for both countries. In addition, the relationships between sources of work stress and coping strategies were significant for both countries. The implications of the findings and recommendations for future research are discussed. The two departments need to develop and improve some regulations, training programs, and other things such as the communication channels.